Increased IL-33 expression in chronic obstructive pulmonary disease - Xia, Jie; Zhao, Junling; Shang, Jin; Li, Miao; Zeng, Zhilin; Zhao, Jianping; Wang, Jianmiao; Xu, Yongjian; Xie, Jungang (American journal of physiology. Lung cellular and molecular physiology, 2015)
Chronic obstructive pulmonary disease (COPD) is an inflammatory lung disease characterized by inflammatory cell activation and the release of inflammatory mediators. Interleukin-33 (IL-33) plays a critical role in various inflammatory and immunological pathologies, but evidence for its role in COPD is lacking. This study aimed to investigate the expression of IL-33 in COPD and to determine whether IL-33 participates in the initiation and progression of COPD. Levels of serum IL-33 and its receptors were measured by ELISA, and serum levels of IL-33, ST2, and IL-1 receptor accessory protein were elevated in patients with COPD compared with control subjects. Flow cytometry analysis further demonstrated an increase in peripheral blood lymphocytes (PBLs) expressing IL-33 in patients with COPD. Immunofluorescence analysis revealed that the main cellular source of IL-33 in lung tissue was human bronchial epithelial cells (HBEs). Cigarette smoke extract and lipopolysaccharide could enhance the ability of PBLs and HBEs to express IL-33. Furthermore, PBLs from patients with COPD showed greater IL-33 release in response to the stimulus. Collectively, these findings suggest that IL-33 expression levels are increased in COPD and related to airway and systemic inflammation. Therefore, IL-33 might contribute to the pathogenesis and progression of this disease.